Reports of the Australasian Antarctic Expedition, 1911–14, and of the British-Australian-New Zealand Antarctic Research Expedition, 1929–31 (Polar Record, 1938)
It is pleasant to be able to record that the printing of the results of the Australasian Antarctic expedition of 1911–14 has been resumed. It will be remembered that the publication of these reports was greatly interfered with by the Great War. During the post-war years the reports were slowly issued from the Government Printing Office, Sydney; but, in 1930, in the absence of financial provision for continuing the work, the printing of the manuscripts was suspended. A resumption of the printing of these reports has now become possible through the good offices of the Minister of Education, Mr D. H. Drumond, largely owing to generous assistance from the Commonwealth Government.